2010
DOI: 10.1038/clpt.2010.20
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Modeling of Biomarker Response to Sunitinib in Healthy Volunteers

Abstract: A pharmacokinetic/pharmacodynamic (PK/PD) study of the tyrosine kinase inhibitor sunitinib was conducted in 12 healthy volunteers using blood pressure and circulating biomarker levels as PD markers. Blood pressure was measured, and plasma concentration-time courses of sunitinib, its major metabolite SU12662, vascular endothelial growth factors VEGF-A and VEGF-C, and soluble VEGF receptor-2 (sVEGFR-2) were studied in healthy subjects receiving 50 mg of sunitinib orally for 3-5 consecutive days. Using NONMEM, PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 35 publications
8
75
0
Order By: Relevance
“…Importantly, Maroto et al have recently highlighted that changes in circulating VEGF have been observed also in samples from healthy volunteers [49,50] and that they could mimic differences attributable to tumor-induced changes in responding patients [51]. Finally, it has been described that interferences between VEGF detection by ELISA and monoclonal antibodies as bevacizumab do exist [52,53].…”
Section: Circulating Biomarkers Vegf and Vegf-related Proteinsmentioning
confidence: 93%
“…Importantly, Maroto et al have recently highlighted that changes in circulating VEGF have been observed also in samples from healthy volunteers [49,50] and that they could mimic differences attributable to tumor-induced changes in responding patients [51]. Finally, it has been described that interferences between VEGF detection by ELISA and monoclonal antibodies as bevacizumab do exist [52,53].…”
Section: Circulating Biomarkers Vegf and Vegf-related Proteinsmentioning
confidence: 93%
“…Of note, sunitinib-induced dose-dependent and reversible increases in circulating plasma VEGF have been observed in nontumor-bearing mice (33) and in healthy humans (34); such nontumor-induced increases in VEGF (and potentially VEGF-related proteins) may mask differences attributable to tumor-induced protein changes in responding versus nonresponding patients. Larger studies are required and the influence of previous treatments and of different VEGF detection methods needs to be carefully considered when assessing VEGF/VEGFR biomarker studies (33,35,36).…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…The LC-MS/MS procedure developed and validated here was used to generate the pharmacokinetic parameters of sunitinib and its active metabolite after administration of 50 mg sunitinib (Sutent TM ) once daily over 3 days (volunteers 1-4) and 5 days (volunteers 5-12) and have recently been reported [25]. In brief, the analytical procedure included blood collection before administration and after 1, 2, 4, 6, 8, 10, 12, 24, 25, 36, 48, 49, 60, 72, 96, 120, 240, 336 and 384 h after the first dose for volunteers 1-4 and additionally after 0.5, 24.5, 48.5, 72.5, 73, 96.5, 97, 98, 100, 102, 104, 106, 108, 144, 168 and 432 h after the first dose for volunteers 5-12.…”
Section: Use Of the Methods During A Pharmacokinetic Study In Human Hementioning
confidence: 99%
“…samples from a pharmacokinetic study that have already been analyzed, we used the samples of a clinical study [25]. A total of 42 samples was analyzed a second time and compared to the results of the first analysis.…”
Section: Precision In Incurred Human Plasma Samplesmentioning
confidence: 99%